إسهامات المجتمع الدولي في مكافحة ظاهرة الهجرة غير الشرعية : Contributions of the International Community in Combating the Phenomenon of Illegal Immigration - Ayoub Anwar Almabrok Husien ,; El Fatih Abdullah Abdelsalam ,; Abdulhamid Mohamed Ali Zaroum , (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
ملخص يهدف هذا البحث إلى التعرف على ظاهرة الهجرة غير الشرعية ومسؤولية المجتمع الدولي تجاه هذه الظاهرة، وكذلك يهدف إلى بيان أسباب ودوافع ومبررات الهجرة غير الشرعية. ولقد اتبع الباحث المنهج الاستقرائي والمنهج المقارن لاستقراء المصادر المتعلقة بماهية الهجرة غير الشرعية. ولقد توصل الباحث إلى العديد من النتائج من بينها: معرفة التطور التاريخي للهجرة غير الشرعية والمراحل التي تعرضت لها الهجرة غير الشرعية منذ بدايتها بعد الحرب العالمية الثانية وصولًا إلى مرحلة تشجيع الهجرة من جانب الدول الأوروبية لتحقيق أهداف التنمية في هذه الدول وصولًا إلى مرحلة وقف الهجرة ومحاربتها. الكلمات المفتاحية: إسهامات. المجتمع الدولي. الهجرة غير الشرعية. Abstract This paper aims to identify illegal immigration phenomenon and the responsibility of the international community towards it. It also aims to identify the causes, motivations, and justifications of illegal immigration. The researcher used both an inductive approach and a comparative approach by drawing upon the literature related to illegal immigration. The researcher found several results, which include: knowing the historical evolution of illegal immigration, and the chronological development of illegal immigration since it started after the second world war until European countries started promoting it for their own development plans, and finally, the stage of putting an end to and fighiting agaisnt illegal immigration. Keywords: Islamic governance, Islamic finance, Algeria, Malaysia